2015
DOI: 10.1007/978-3-319-16006-1_18
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Impacts—Marine Biogeochemistry

Abstract: Marine biogeochemistry deals with the budgets and transformations of biogeochemically reactive elements such as carbon, nitrogen and phosphorus. Inorganic nitrogen and phosphorus compounds are the major nutrients and control organic matter (biomass) production in the surface water. Due to various anthropogenic activities, the input of these nutrients into the Baltic Sea has increased drastically during the last century and has enhanced the net organic matter production by a factor of 2-4 (eutrophication). This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 171 publications
0
12
0
Order By: Relevance
“…Pelagic primary production can however contribute to surface water A T , when the organic matter is exported. With respect to alkalinity trends in the Baltic Sea surface water, it is reasonable to assume that nitrate based primary production and thus the A T contribution increased along with nutrient inputs that peaked around 1980 (Gustafsson et al ; Schneider et al ). However, recent modelling studies suggest that the previously increasing nitrogen uptake by phytoplankton levelled off around 1990 (Gustafsson et al ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pelagic primary production can however contribute to surface water A T , when the organic matter is exported. With respect to alkalinity trends in the Baltic Sea surface water, it is reasonable to assume that nitrate based primary production and thus the A T contribution increased along with nutrient inputs that peaked around 1980 (Gustafsson et al ; Schneider et al ). However, recent modelling studies suggest that the previously increasing nitrogen uptake by phytoplankton levelled off around 1990 (Gustafsson et al ).…”
Section: Discussionmentioning
confidence: 99%
“…This implies that a reliable acidification estimate cannot solely be based on the atmospheric pCO 2 evolution. Previous studies indeed suggested that the alkalinity in the eastern Gotland Sea increased by around 100 µmol kg −1 (∼6%) from 1930 to 2010 (Schneider et al ). Extensive A T measurements were performed in the Baltic Sea region with investigations dating back to the early 20 th century (Buch ; Hjalmarsson et al ).…”
Section: Introductionmentioning
confidence: 91%
“…All treatments were superimposed on the natural fluctuations of all environmental variables. The elevated levels of both factors were chosen according to climate change predictions for shallow coastal Baltic habitats over the next 100 years (Elken et al ; Schneider et al ).…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…Due to anthropogenic global change, ocean warming and acidification may singly or interactively affect photophysiological performance of Fucus during the different seasons. Fucus was exposed to single and combined treatments of elevated seawater temperature ( + 5 • C) and pCO 2 (1100 ppm) in all four seasons as predicted for shallow coastal Baltic habitats for the year 2100 (Elken et al, 2015;Schneider et al, 2015;Müller et al, 2016). These scenarios, including natural fluctuations forced by diurnal and seasonal changes, atmospheric and hydrographic conditions, were simulated using benthic mesocosms [Kiel Outdoor Benthocosms (KOBs), Wahl et al, 2015a].…”
Section: Introductionmentioning
confidence: 99%